Pengaruh padat tebar yang berbeda terhadap tingkat kelangsungan hidup dan laju pertumbuhan ikan lele (Clarias gariepinus) - Muh Ishar Difinubun Ari; Ainul Alim Rahman; Sipriana Siana Tumembouw (e-Journal BUDIDAYA PERAIRAN, 2023)
Intensive cultivation activities that have now been developed cause many problems of damage to the cultivation environment due to high stocking densities. With the rise of aquaculture technology, it is necessary to conduct research on alternative methods of cultivation with high stocking densities that do not have an adverse impact on environmental sustainability and good fish quality. This research was conducted in December 2022-February 2023 using a tarpaulin pond. The aim of the study was to determine the effect of different stocking densities on the survival rate and growth rate of the Dumbo catfish (Clarias gariepinus). This study used an experimental method using a completely randomized design (CRD) with 3 treatments and 3 replications using stocking densities of 250, 500 and 750 individuals/m3. The main parameters in this study were survival rate and growth rate, while the supporting parameters in this study were water quality (temperature, pH, DO, ammonia, nitrate and nitrite). The results obtained from this study were the average survival rate of catfish (C. gariepinus) for treatment A (250 individuals/m3) of 88.5%, treatment B (500 individuals/m3) of 7.15% and treatment C (750 head/m3) of 82.9%. The daily growth rate of catfish (C. gariepinus) for treatment A (250 individuals/m3) was 7.25% body weight/day, treatment B (500 individuals/m3) was 7.15% body weight/day, and treatment C (750 head/m3) of 6.91% body weight/day. Water quality during maintenance is still in the normal range, with a temperature of 27.3-30.9 0C. pH of 8.28-8.61. DO of 1.41-5.68 mg/l. ammonia of 0.3-3.5 mg/l. nitrite of 0.02-0.09 mg/l and nitrate of 2.12-2.79 mg/l. The results of this study cannot be concluded that different stocking densities have no effect on survival rate and growth rate of catfish (Clarias gariepinus). Keywords: Intensive cultivation, water quality, environment degradation